THE PROBLEM OF TEACHER PREPARATION FOR PERSONALLY ORIENTED EDUCATION OF PRIMARY SCHOOL STUDENTS - L.V. Kondrashova (Academy of Cognitive and Natural Sciences, 2010)
The creative ability of the child. Why and why they need to develop? The article discusses the main directions of development of creative writing junior pupils are shown the realization of their abilities in the classroom reading.